Synergism between inhibitors of Aurora A and KIF11 overcomes KIF15‐dependent drug resistance - Ma, Hoi Tang (Mol Oncol, 2014)
The mitotic kinesin KIF11 (also called Eg5) plays critical roles in spindle functions. Although a number of small‐molecule inhibitors of KIF11 are currently in clinical development, drug‐resistance could be developed through compensation by another kinesin called KIF15. Using a newly developed infrared‐based cell system, we discovered that the effectiveness of one of the latest generations of KIF11 inhibitor (SB743921) could be enhanced with several inhibitors of Aurora A kinase. Evidence including live‐cell imaging and isobologram analysis indicated that targeting KIF11 and Aurora A together promoted monoastral spindle formation and mitotic catastrophe synergistically, supporting a model of parallel pathways of centrosome regulation by Aurora A and KIF11. We also developed a KIF15‐dependent SB743921‐resistance cell model. Significantly, the drug‐resistance could also be overcome with Aurora A inhibitors. These results provide a molecular basis for increasing the effectiveness of Aurora A and KIF11 inhibitors and tackling problems of drug resistance.